Evaluation of Chitosan-Based Nanoparticles in Oral Delivery of Insulin - Wong, Chun Yuen Jerry (Curtin University, 2020)
Diabetes mellitus is a chronic metabolic disorder. To improve patient compliance and alleviate the unwanted side effects that are associated with insulin injections, the project aimed to evaluate the potential of nanoparticles in oral delivery of insulin. The developed nanoparticles maintained the bioactivity of the entrapped insulin, and demonstrated a balance in mucoadhesiveness strength and muco-penetrating capacity. The nanoparticles could preserve the physicochemical properties upon storage, and induce glucose uptake in skeletal muscle cells.